Looking for spectroscopic families among diffuse interstellar bands - Wszolek, B.; Szumlas, M.; Wlodek, N. (Известия Крымской астрофизической обсерватории, 2007)
Among the diffuse interstellar bands (DIBs), observed in the spectral range from 5590 to 6830 angstroms, we have searched for some candidates to be spectral ’relatives’ of DIBs at 5780 and 5797 angstroms. We have found that structures at 5719, 5766, 5769, 5773, 5793, 5819, 5829, 5850, 6090, 6439, 6449 and 6492 angstroms are good candidates to belong to 5797 spectroscopic family. On the other hand, DIBs 5776, 5795, 6108, 6162, 6597, 6793, 6795, 6827 tend to belong to the family of 5780.